Democracy in the Classroom: 'It’s All About Participation' - Hartveit Lie, Janaina; Endresen-Maharaj, Kristin; Dahlen Svendsen, Mathilde (Journal of Teaching and Learning, 2026)
This article investigates teachers’ conceptions of democracy, citizenship, and participation in Norwegian upper secondary vocational education and training (VET). While there is ample research on students’ understanding of democracy, less research has focused on how teachers understand the concept. Democracy and citizenship are among three interdisciplinary topics in Norway’s LK20 curriculum, and participation has a central place in both the curriculum and the Education Act, making this study both timely and important in the Norwegian context. This paper examines how the participating teachers understood the concepts of democracy, citizenship, and participation, their teaching of those concepts, and their classroom instruction. This qualitative study draws upon six semi-structured interviews with teachers working in an upper secondary school, whose principal recruited three female and three male teachers of common-core subjects in vocational study programs. The data were analyzed through meaning compression. The findings suggest that teachers view democracy and citizenship as broad, diffuse concepts, yet the concept of participation contributes to making democracy education more concrete and manageable. The study can enhance teachers’ understanding of the concepts of democracy, citizenship, and participation, as well as the type of democracy education students receive in their daily experiences.